Islam Jawa: Dari mitis ke Epistemologis - Agnesius, Marselus (Perspektif, 2007)
Before the coming of Islam, Javanese society was and is still - very much coloured by Hinduism, Buddhism and local religious believes. It formed some sort of religious syncretism. Islamic teachers found that it was very difficult to convert Javanese to Islam, unless a process of inculturation would be initiated. This decision proves to be the perfect step, as the Javanese start to consider Islam as a force that respects their local customs. The interaction that follows has transformed Javanese society and vice versa. Islam trans- forms Javanese society and Javanese society transformed Islam. In this article, the author presents some historical facts as back grounds, how the Javanese cultures has developed under the influence of different religious believes: Hinduism, Buddhism, local believes and Islam. This interaction forms a new model of culture which very much influences modern Javanese society. What remain intact is the spirit of mysticism. Contrast to the missionary character to Islam, Javanese society accepts Islam but also maintain the spirit of mysticism. Using the "Serat Suluk Saloka Jiwa" as an example, the author argues that for many Javaneses, the spirit of mysticism cannot be taken away, regardless the common practice of Islam demands so. Therefore, the author suggest that there should be a movement to move from the way to A Sunderstand Islam, leaving the mystical understanding and adopting epistemological approach. The author also insists, that this process can serve as a model for the actual situation in Indonesia.